Accomplished Minimum-process Synchronized Consistent Recovery Line Aggregation Algorithm for Fault-Tolerant Mobile Computing Environments - Sanjiv Sharma, Munish Kumar, Keerti Shrivastva, Sanjeev Kumar, Deepak Chandra Uprety (Mathematical Statistician and Engineering Applications, 2022)
We scheme a minimal-collaborating-proceeding coordinated CRL-aggregation (Consistent Recovery Line Aggregation) arrangement for non-deterministic mobile distributed interconnections, where no inoperable retrieval-points are arrested. We use the following technique to minimize the intrusion of proceedings. During the timeline, when a proceeding dispatches its causal-interrelationship set to the instigator and acquires the minimal-collaborating-set, may acquire some computation-messages, which may add new members to the already computed minimal-collaborating-set. Such computation-messages are delayed at the receiver side. It should be noted that the duration for which the computation-messages are delayed at the receiver’s end is negligibly small. We also try to minimize the loss of CRL-aggregation effort when any proceeding flops to arrest its retrieval-point in harmonization with others. We scheme that in the first phase, all pertinent Mbl_Nods (Mobile Modes) will arrest evanescent retrieval-point only. Evanescent retrieval-point is stored on the memory of Mbl_Nod only. In this case, if some proceeding flops to arrest retrieval-point in the first phase, then Mbl_Nods need to discard their evanescent retrieval-points only. The effort of arresting an evanescent retrieval-point is negligible as compared to the quasi-persistent one. In the schemed arrangement, the harmonization with the instigator Mbl_Suppt_Stn is done without dispatching explicit control-messages. We want to emphasize that in all coordinated CRL-aggregation schemes available in literature, harmonization among proceedings and instigator takes place by dispatching explicit control-messages. In this way, we try to significantly reduce the harmonization overhead in coordinated CRL-aggregation .